Performance Analysis of Induction Motor Drives under Nonlinear Load Conditions - C.Arun Prasath (National Journal of Electrical Electronics and Automation Technologies, 2025)
This paper proposes studies on the dynamic performance, and operational stability of induction motor, drives under nonlinear load condition, which is a common phenomenon in industrial installations used for arc furnace, conveyors, and reciprocating compressors. A detailed comparative analysis has been given between voltage-source inverter (VSI) fed and direct torque control (DTC) based IM drives from MATLAB/ Simulink simulation results. Fundamental performance indicators of interest include torque ripple, harmonics present in the stator current, speed regulation and overall system efficiency. A nonlinear load model with variable components of torque and harmonic disturbances is created to simulate real-time mechanical nonlinearity. Testing on a 5 HP induction motor prototype shows that DTC has better torque response and hardness compared to VSI, which has a lower total harmonic distortion (THD). The results offer a practical lesson of selection and control strategy adaptation for induction motor drives under unflattering load situations.